Valuing Green Infrastructure : Case Study of Kali Gandaki Watershed, Nepal - World Bank Group (World Bank, Washington, DC, 2019)
Watersheds are an appropriate and effective unit for managing ecological assets, given the interconnected nature of economic activities and their impacts within a watershed, locally and regionally, upstream and downstream. Watersheds are increasingly recognized as a critical form of green infrastructure that provides a flow of economic benefits. In mountainous countries like Nepal, watershed management can contribute to important development goals and increase resilience to climate change. Watershed management can refer to a wide variety of practices that fall under the umbrella of investment in green infrastructure, such as slope correction using terracing, planting hedgerows and cover crops, using crop residues, cover crops, and mulches, trenching and bunding, re- and afforestation, and revision of grazing practices. Minimizing the loss of soil and downstream sedimentation is one of the most visible and immediate benefits of watershed management, whose positive impact can be felt across many sectors of the economy, including agriculture, hydropower, and water. This study focuses on the watershed area that drains to the Kaligandaki, Nepal. The study presents a systematic approach to assess where, in what quantity, and through what processes sediment is being generated in the Kali Gandaki Basin, identify plausible interventions through investing in green infrastructure approaches for watershed management, and evaluate their impacts.